A curious case of an orbit lesion in a young girl: A curious case of an orbit lesion in a young girl: Case report and Literature review - Alkhairy, Saba (Pakistan Journal of Ophthalmology, 2020)
To present a case report of a 15 year old girl presenting with a slow growing mass in the orbit with normal visual acuity. We followed the patient for a year and closely observed the increase in the size of the mass for over a year both clinically and radiologically. The mass grew gradually with no effect on her visual acuity which was 6/6 in both eyes using Snellen chart; pupillary reactions were normal with no afferent papillary defect and her extraocular movements were full. Her anterior segment and posterior segment of the eye including the optic disc and macula and the intra ocular pressure remained within normal limits. We then had to intervene surgically on request of the patient as the mass had caused significant cosmetic disfigurement .It was a combined effort by an ENT and an eye surgeon for the effective and complete removal of the lesion.We did a frontal orbitotomy under general anesthesia and the mass recovered was sent for biopsy. The biopsy report concluded the mass to be juvenile psammomatoid ossifying fibroma. Key words: Orbit,psammomatoid ossifying fibroma,frontal orbitotomy